2020
DOI: 10.1523/eneuro.0090-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Representation of Tactile Numerosity in Working Memory

Abstract: Estimated numerosity perception is processed in an approximate number system (ANS) that resembles the perception of a continuous magnitude. The ANS consists of a right lateralized frontoparietal network comprising the lateral prefrontal cortex (LPFC) and the intraparietal sulcus. Although the ANS has been extensively investigated, only a few studies have focused on the mental representation of retained numerosity estimates. Specifically, the underlying mechanisms of estimated numerosity working memory (WM) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…A candidate region for this function is the premotor cortex (PMC) which is routinely found to be activated during WM (Carpenter, Baud-Bovy, Georgopoulos, & Pellizzer, 2018;Marvel, Morgan, & Kronemer, 2019;Rottschy et al, 2012;Simon et al, 2002) and is involved in prospective attention during sequence processing (Schubotz, 2004). Recently, Fegen, Buchsbaum, and D'Esposito (2015) reported that activation in the PMC was modulated by WM load and rehearsal rate in a verbal WM study and we have repeatedly demonstrated the involvement of the PMC in tactile WM (Schmidt et al, 2017;Uluç, Velenosi, Schmidt, & Blankenburg, 2020;Velenosi, Wu, Schmidt, & Blankenburg, 2020;Wu et al, 2018). Together, these reports motivate further investigation into the functional contribution of the PMC to the rehearsal process, in particular its involvement in the reactivation of content-specific codes.…”
supporting
confidence: 66%
“…A candidate region for this function is the premotor cortex (PMC) which is routinely found to be activated during WM (Carpenter, Baud-Bovy, Georgopoulos, & Pellizzer, 2018;Marvel, Morgan, & Kronemer, 2019;Rottschy et al, 2012;Simon et al, 2002) and is involved in prospective attention during sequence processing (Schubotz, 2004). Recently, Fegen, Buchsbaum, and D'Esposito (2015) reported that activation in the PMC was modulated by WM load and rehearsal rate in a verbal WM study and we have repeatedly demonstrated the involvement of the PMC in tactile WM (Schmidt et al, 2017;Uluç, Velenosi, Schmidt, & Blankenburg, 2020;Velenosi, Wu, Schmidt, & Blankenburg, 2020;Wu et al, 2018). Together, these reports motivate further investigation into the functional contribution of the PMC to the rehearsal process, in particular its involvement in the reactivation of content-specific codes.…”
supporting
confidence: 66%
“…To test that the participants had not counted the number of all dots in the applied stimuli, we performed a number naming test after the participants left the MRI scanner. To assess the highest numerosity in our stimulus set for which participants were able to name the exact number of dots, we used a modified version of a number naming test applied in Spitzer, Fleck, and Blankenburg (2014) and Uluç, Velenosi, Schmidt, and Blankenburg (2020). In each trial participants were presented with one stimulus, for 700 ms as applied in the DMTS task, and had to report the exact number of dots by typing it in on a keyboard.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, given the role in sensorimotor integration and action guidance played by these areas, it is likely that they are implicated in the behavioral interactions between numerosity and action. Together with the prefrontal cortex, implicated in the maintenance of working memory of supramodal (visual, auditory, and tactile) numerosity information [44,45], and with the mediotemporal regions containing numerosity selective neurons [27], these parietal areas may constitute the neural substrate of the proposed sensorimotor number system in humans. Although these hypotheses are largely speculative, the anatomical proximity of areas recruited for numerosity and action processing could favor their interaction, as has been proposed for numerosity and size processing [46].…”
Section: Numerosity and Action In The Human Brainmentioning
confidence: 99%